Study protocol for a randomised controlled trial evaluating the benefits from bimodal solution with cochlear implant and hearing aid versus bilateral hearing aids in patients with asymmetric speech identification scores - Jesper Hvass Schmidt; Yeliz Jakobsen; Lou-Ann Christensen Andersen (BMJ Open)
Introduction Cochlear implant (CI) and hearing aid (HA) in a bimodal solution (CI+HA) is compared with bilateral HAs (HA+HA) to test if the bimodal solution results in better speech intelligibility and self-reported quality of life.Methods and analysis This randomised controlled trial is conducted in Odense University Hospital, Denmark. Sixty adult bilateral HA users referred for CI surgery are enrolled if eligible and undergo: audiometry, speech perception in noise (HINT: Hearing in Noise Test), Speech Identification Scores and video head impulse test. All participants will receive new replacement HAs. After 1 month they will be randomly assigned (1:1) to the intervention group (CI+HA) or to the delayed intervention control group (HA+HA). The intervention group (CI+HA) will receive a CI on the ear with a poorer speech recognition score and continue using the HA on the other ear. The control group (HA+HA) will receive a CI after a total of 4 months of bilateral HA use.The primary outcome measures are speech intelligibility measured objectively with HINT (sentences in noise) and DANTALE I (words) and subjectively with the Speech, Spatial and Qualities of Hearing scale questionnaire. Secondary outcomes are patient reported Health-Related Quality of Life scores assessed with the Nijmegen Cochlear Implant Questionnaire, the Tinnitus Handicap Inventory and Dizziness Handicap Inventory. Third outcome is listening effort assessed with pupil dilation during HINT.In conclusion, the purpose is to improve the clinical decision-making for CI candidacy and optimise bimodal solutions.Ethics and dissemination This study protocol was approved by the Ethics Committee Southern Denmark project ID S-20200074G. All participants are required to sign an informed consent form.This study will be published on completion in peer-reviewed publications and scientific conferences.Trial registration number NCT04919928.